2020
DOI: 10.48550/arxiv.2007.06524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tensor-based techniques for fast discretization and solution of 3D elliptic equations with random coefficients

Abstract: In this paper, we propose and analyze the numerical algorithms for fast solution of periodic elliptic problems in random media in R d , d = 2, 3. We consider the stochastic realizations using checkerboard configuration of the equation coefficients built on a large L × L × L lattice, where L is the size of representative volume elements. The Kronecker tensor product scheme is introduced for fast generation of the stiffness matrix for FDM discretization on a tensor grid. We describe tensor techniques for the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…From the viewpoint of mathematical analysis, this article is a natural continuation of previous work by Khoromskaia et al [26,27], where quantitative homogenization results for random media were confirmed by numerical simulations. Indeed, we go beyond the cited work by investigating microstructure models of higher complexity, as is required for engineering applications.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…From the viewpoint of mathematical analysis, this article is a natural continuation of previous work by Khoromskaia et al [26,27], where quantitative homogenization results for random media were confirmed by numerical simulations. Indeed, we go beyond the cited work by investigating microstructure models of higher complexity, as is required for engineering applications.…”
Section: Discussionsupporting
confidence: 57%
“…We carry out numerical experiments to quantify the systematic and the random error for composite microstructures. In contrast to previous works [26,27], we use microstructures of industrial relevance and complexity, utilizing real physical parameters, investigating spherical and cylindrical fillers. While the ensembles considered here do not fall into the class considered in the theory -they are neither finite range nor a suitable functional inequality is known, see, however, Duerinckx & Gloria [28,29] -we expect that they belong to the same universality class.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer the reader to [14] and [18] for extensive reviews on tensor theory and extended analysis of tensor decompositions and their numerous applications. Tensor formats are also used for solving time-dependent and stochastic/parametric PDEs ( [16], [1]). Other families of methods called Proper Generalized Decomposition (PGD) methods use tensor decomposition in high dimensional problems [26], [25].…”
mentioning
confidence: 99%